Development of a test for recording both visual and auditory reaction times, potentially useful for future studies in patients on opioids therapy - Miceli L; Bednarova R; Rizzardo A; Samogin V; Della Rocca G (Dove Medical Press, 2015)
Luca Miceli,1 Rym Bednarova,2 Alessandro Rizzardo,1 Valentina Samogin,1 Giorgio Della Rocca1 1Department of Anesthesia and Intensive Care Medicine, University of Udine, 2Department of Pain Medicine and Palliative Care, Hospital of Latisana, Latisana, Udine, Italy Objective: Italian Road Law limits driving while undergoing treatment with certain kinds of medication. Here, we report the results of a test, run as a smartphone application (app), assessing auditory and visual reflexes in a sample of 300 drivers. The scope of the test is to provide both the police force and medication-taking drivers with a tool that can evaluate the individual’s capacity to drive safely. Methods: The test is run as an app for Apple iOS and Android mobile operating systems and facilitates four different reaction times to be assessed: simple visual and auditory reaction times and complex visual and auditory reaction times. Reference deciles were created for the test results obtained from a sample of 300 Italian subjects. Results lying within the first three deciles were considered as incompatible with safe driving capabilities. Results: Performance is both age-related (r>0.5) and sex-related (female reaction times were significantly slower than those recorded for male subjects, P<0.05). Only 21% of the subjects were able to perform all four tests correctly. Conclusion: We developed and fine-tuned a test called Safedrive that measures visual and auditory reaction times through a smartphone mobile device; the scope of the test is two-fold: to provide a clinical tool for the assessment of the driving capacity of individuals taking pain relief medication; to promote the sense of social responsibility in drivers who are on medication and provide these individuals with a means of testing their own capacity to drive safely. Keywords: visual reaction time, auditory reaction time, opioids, Safedrive